Gambaran Tingkat Kepatuhan Perawat dalam Implementasi Enam Sasaran Keselamatan Pasien: A Systematic Literature Review - Sumadniati Sumadniati; Raden Ahmad Dedy Mardani; Zul Hendri (Universitas Malahayati Lampung, 2026)
ABSTRACT Patient safety is a global health priority, with nurses playing a crucial role in implementing the Six Patient Safety Goals (SPSG). However, nurse compliance levels vary significantly across different contexts and dimensions of SPSG.This systematic literature review aimed to analyze the level of nurse compliance in implementing the Six Patient Safety Goals based on current scientific evidence (2020-2025). A systematic literature review was conducted using Scopus and Web of Science databases with keywords